Human Umbilical Cord Blood Derived-Mesenchymal Stem Cells Alleviate Dextran Sulfate Sodium-Induced Colitis by Increasing Regulatory T Cells in Mice - Li, Ying; Ma, Ke; Zhang, Luping; Xu, Hong; Zhang, Nan (Frontiers in Cell and Developmental Biology, 2020)
Inflammatory bowel disease (IBD), which main clinical manifestations include abdominal pain and diarrhea occurring repeatedly, is a kind of autoimmune disease. It has been reported in preceding studies that mesenchymal stem cells (MSCs) can reduce inflammation by regulating the function of immune cells. But studies about the interaction between MSCs and adaptive immune cells, especially in IBD models, are insufficient. Therefore, the objective of this research was to estimate the therapeutic effects of mesenchymal stem cells from human umbilical cord blood (hUCB-MSCs) in an IBD model of rodent and to clarify the therapeutic mechanisms of hUCB-MSCs. Dextran sulfate sodium (DSS) was used to induce colitisin rodent. Mice with colitis were treated with intraperitoneal infusions of hUCB-MSCs and evaluated for mortality and diverse disease symptoms containing weight reduction, diarrhea, and bloody stools. The levels of histopathologic severity and generation of regulatory T cells (Treg) were also determined. Treatment with hUCB-MSCs ameliorated the clinical and histopathologic severity of acute and chronic colitis in mice. Furthermore, T cell infiltration into the inflamed colon was significantly decreased(p=0.0175), and Foxp3+ cells were substantially higher in the hUCB-MSC group than that of the DSS group. Our results suggest that hUCB-MSCs are able to alleviate inflammation via adding Foxp3+ Tregs in an IBD model of mouse. As a result, these findings suggest the opportunity of hUCB-MSC being applied to patients with IBD.